ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR YANG BEKERJA DI SEKTOR INFORMAL - Rayung Wulan, Sri Endang (Jurnal de Facto, 2014)
In comliance with commendation The Constitution Code of Numbeer 23 The Year 2002 about â€œChild Protectionâ€. Words mastered by this protection bearing the conept of human right. Hence child are have right to protection, to give opinion and for their interest to be reconized and protection the law even since the first ( Section 52 subsection 2 ) The Constitution Code Of Number 39 The Year 1999 about Human Rights. Child protection measures need to be implemnted as early as possible, that since from in the womb of the child 18 (eighteen) years old. The role of goverment, parents, and the community is very important to protect children.